Statistics education in medical sciences - (:unkn) unknown (My University, 2002)
Objective: Although there has been a popular trend in using statistics in medical sciences in recent years, there are still some difficulties in relating and applying the knowledge of statistics. The aim of this study is to determine common problems and to find solutions to these problems. Methods: A questionnaire was given out to 147 Marmara University Medical School academic and non-academic staff. The academic staff consisted of professors associate professors, assistant professors and instructors, whereas non-academic staff consisted of doctorate, residency and master of sciences students. Results: It has been observed that 59.2 % of the participants were not interested in biostatistics courses during their education, and their major reason was that "Participants could not provide the fundamental concepts and techniques of statistics with an understanding of the terms used in experimental and clinical studies". However, they believed in the necessity of statistics in health sciences and biostatistical consultance in their scientific researches. "Teaching statistical concepts using computers" was the answer most chosen answer. The most common answers for determining why knowledge of statistics, was needed in their researches were, "analyzing data", "inferring and interpreting the results" and "modeling". Conclusion: There is a great need for biostatistical knowledge in medical scientific research.
Keywords: Biostatistics; Education; Necessity